About Some Features of The “Color Picture of The World” of The Russian and Uzbek Languages, Reflected in Phraseologists - Kodirova Feruza Kahramanovna (International Journal of Scientific Trends, 2024)
The purpose of this article is to determine the similarities and differences between Russian and Uzbek phraseological units that reflect the linguistic and color picture of the world. The names of flowers in different languages are taken not only literally, they have a symbolic nature. The peculiarities of the color vision of the world by representatives of different ethnocultural communities allow us to speak about the existence of an ethnic national color picture of the world. Such differences between different peoples in cultural ideas about color are most clearly manifested in associations that indicate the national and cultural specificity of thinking. This work presents the features of the linguistic color picture of the Russian and Uzbek languages, which are reflected in phraseological units, and also identifies differences and similarities in the semantic connotations of color components.